Standing up the space force: Knowns and unknowns. Issue 4 (4th July 2019) - Handberg, Roger
Abstract: Creation of a Space Force became possible when President Trump announced his decision to support such an organization. This followed on earlier congressional efforts to create a Space Corps, one that failed. Presently, the U.S. is working on the organizational possibilities ranging from a unified command, an independent sixth military service, or some other variant. The larger question is how such a force changes international understandings regarding military space operations. Such an effort draws a response from other space powers, exactly what that entails remains unclear. This effort raises the prospects for weaponization of outer space, creating a situation of strategic instability, given the vulnerability of space craft to interception and attacks both kinetic and electronic. Long term, the struggle is over whether space weaponization will totally undermine existing prohibitions on weapons of mass destruction, specifically nuclear. The prospects are heightened for an arms race in space including nuclear weapons.